Piscirickettsia salmonis-Triggered Extracellular Traps Formation as an Innate Immune Response of Atlantic Salmon-Derived Polymorphonuclear Neutrophils - Pablo Alarcon; Gabriel Espinosa; Catalina Millan; Julia Saravia; Vania Quinteros; Ricardo Enriquez; Claudio Henriquez; Luis Vargas-Chacoff; Rafael A. Burgos; Anja Taubert; Carlos Hermosilla; Francisco J. Morera (Biology, 2021)
Extracellular traps (ETs) are webs of DNA, citrullinated histones, anti-microbial peptides, and proteins that were not previously reported in Atlantic salmon (Salmo salar). ETs are mainly released from polymorphonuclear neutrophils (PMN) and are considered a novel PMN-derived effector mechanism against different invasive pathogens. Here, we showed that Atlantic salmon-derived PMN released ETs-like structures in vitro in response to highly pathogenic facultative intracellular rickettsial bacteria Piscirickettsia salmonis. PMN were isolated from pre-smolt Atlantic salmon and stimulated in vitro with oleic acid and P. salmonis. Extracellular DNA was measured using the PicoGreen™ dye, while immunofluorescence image analysis was used to confirm the classical components of salmonid-extruded ETs. Future studies are required to better understand the role of Atlantic salmon-derived ETs orchestrating innate/adaptive immunity and the knowledge on regulation pathways involved in this cell death process. Thus, comprehension of salmonid-derived ETs against P. salmonis might represent novel alternative strategies to improve host innate defense mechanisms of farmed salmon against closely related rickettsial bacteria, as a complement to disease prevention and control strategies.